Legal implications of the judicial judgment on oral emergency anticonception - Chapa-Romero, Jacqueline (2019)
Emergency oral contraception based on levonorgestrel prevents pregnancy by preventing or delaying ovulation. The factual medical-legal analysis based on the judicial ruling regarding compliance in the health facilities is performed to guarantee the delivery of the emergency oral contraception pill to the patients, otherwise the precautionary measure has not been effective in ensuring delivery of the medication and in other cases barriers to its dispensation have been observed.